Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Pelecehan Seksual (Studi Kasus Di Polres Ngawi) - Handayani, Dewi; , Kuswardhani, S.H., M.Hum (2016)
The Cases of child sexual abuses are continues to increase over time. Children are the nation's future generation who need special legal protection which is different from adults, because of their immaturity physical and mental reasons. The legal protection of children is defined as the legal protection to the children's freedom and rights which is related to the welfare. The purpose of this research is to determine how the legal protection and the obstacle factors related to the crime of child sexual abuse victims in Ngawi. The method used in this research is empirical juridical approach with descriptive study. The data sources consists primary data and secondary data. The Data collected from literature study and interviews. Data were analyzed using qualitative approach, that is primary data obtained directly from the field analyzed according to the legislations which is related to the child protection.